DISKRESI DAN TANGGUNGJAWAB ADMINISTRASI PEMERINTAHAN - Julista Mustamu (Faculty of Law, Universitas Pattimura, 2011)
In a modern State law (Welfare State), granting discretion to government is inevitable as the weaknesses or limitations of legislation and in accordance with the dynamic activities of the government in performing public services in the community is growing rapidly. The use of discretion should not be freely, in the sense that must not conflict with the general principles of good governance and should not be contrary to public interest.